Implementation of the nursing service in podiatria clinic in public outpatient health unit (Research, Society and Development, 2021)
Objective: to describe the implementation of a Nursing service in Podiatry Clinic in a public health unit in the State of Rio de Janeiro. Method: convergent care research describing the service implementation process. Results: the evaluation of the implementation of the service provided the performance of one thousand eighty-five visits in three years, contributing significantly to the reduction of complications and injuries in patients with diabetes. In addition, it contributed to the qualified professional training of sixty-four nurses who qualified in the podiatry a clinic area, in the city of Rio de Janeiro, through the extension course. Conclusion: the implementation of the Clinical Podiatry service contributed to the reduction of complications of diabetic foot, besides providing better quality of nursing care offered to the clientele of the Unified Health System through specialized care, besides contributing to the training of professionals with interest in the area seeking qualification.